Shear friction and fracture based model for reinforced concrete beams with recycled materials - Brian Jacks Odero; Raphael Mutuku; Timothy Nyomboi; Zachary Abiero Gariy (Alexandria Engineering Journal, 2023)
Shear resistance by beams without stirrups presents the transfer of shear and normal principal stresses across the open cracks within reinforced concrete (RC) beams. The complexity of the shear mechanism is further complicated by the distorted structure of RCA, which is composed of hardened adhered surface mortar and virgin aggregate. Compression field theory (CFT) postulates a series of curves for shear-loaded beams to signify the transfer of tensile and compressive stresses in concrete beams across developed shear cracks. Special attention is given to beams with recycled materials, which do not necessarily give the same strength as virgin aggregate. A numerical shear model is developed that accounted for the fracture characteristics, modes I and II of the beam containing RCA along the primary crack path from dowel action, aggregate interlock, and uncracked compression zone of the beam. The model captures the correlation of shear arm ratio, longitudinal reinforcement ratio, maximum coarse aggregate size, and concrete strength. The study model was validated using experimental results from 139 concrete beams containing RCA without stirrups. The strength ratio resulted in mean of 1.32 with a standard deviation of 0.48, a coefficient of variation of 36.8% and R-squared value of 0.65. The statistical evaluations of the model were compared with the other nine (9) theoretical models by authors and codes of practice. The developed model predicted a relatively higher shear strength value due to the inclusion of contribution from dowel action, aggregate interlock and compression zone.